Pengembangan Metode Pembelajaran Yang Efektif di Taman Pendidikan Al-Qur'an (Studi Kasus di Taman Ilmu Zainun Nafi' Singosari Malang) - Eny Mujayanah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to determine the method of learning the Qur'an and the effectiveness of learning at the Zainun Nafi Science Park. This research used a qualitative research as the method. The observation, interviews, and documentation become data collection procedure for this research. For checking the validity of the data, this research is using data triangulation techniques that is divided into three stages, explicitly triangulation techniques, time, and sources. Data analysis is carried out into three stages, namely data reduction, data presentation, and conclusion verification. The results of this study shows that the method of learning the Qur'an at the Zainun Nafi Science Park used the Ummi method. The implementation of the Ummi method in learning the Qur'an at Zainun Nafi Science Park has been running well and in accordance with the system proposed by the Ummi Foundation, both in terms of learning materials, achievement targets, and learning stages. Resorting to the activities, 7 stages of learning must be passed such as opening, appreciating, planting concepts, understanding concepts, practicing, evaluating, and closing. Al-Qur'an learning is carried out from Monday to Friday with a duration of 60 minutes. The learning process uses the classical method of reading and listening, the time required to complete the material for 40 meetings, and it can be faster than the predetermined target. The main elements of the Ummi method are Ummi's 3 strengths, namely methods, systems, and quality teachers. Each method certainly has advantages and disadvantages for its application in an institution and overcome the shortcomings of the application of the Ummi method. Thus, Zainun Nafi Science Park conduct internal and external supervision, manage an evaluation of the Qur'an teacher once a week, and cooperate with parents through parenting as well as holding a home visit program.